Storage conditions and adsorption thermodynamic Propertiesfor purple Corn - Choque Quispe, David (2022)
Adsorption isotherms provide insight into the thermodynamic properties governed by food storage conditions. Adsorption isotherms of purple corn of the Canteño variety were evaluated at 18, 25, and 30 C, for the equilibrium relative humidity (ERH) range between 0.065 and 0.95. The equilibrium moisture (Xe) was determined by the continuous weight-change method. Seven mathematical models of isotherms were modeled, using the coefficient of determination R2, mean absolute error (MAE), and estimated standard error (ESE) as the convergence criterion. Thermodynamic parameters such as isosteric heat (qst), Gibbs Free Energy (DG), differential entropy (DS), activation energy (Ea), and compliance with the isokinetic law were evaluated. It was observed that the adsorption isotherms presented cross-linking around 75% ERH and 17% Xe, suggesting adequate storage conditions at these values. The GAB and Halsey models reported better fit (R2 > 97%, MAE < 10%, ESE < 0.014 and random residual dispersion). The reduction of Xe from 17 to 7%, increases qst, from 7.7022 to 0.0165 kJ/g, while DG decreases considerably with the increase in Xe, presenting non-spontaneous endergonic behavior, and linear relationship with DS, evidencing compliance with the isokinetic theory, governed by qst. Ea showed that more energy is required to remove water molecules from the upper layers bound to the monolayer, evaluated using CGAB. The models predicted the storage conditions, and the thermodynamic parameters show the structural stability of the purple corn grains of the Canteño variety during storage.